2019
DOI: 10.3390/hydrology6020049
|View full text |Cite
|
Sign up to set email alerts
|

Application of Meteorological and Hydrological Drought Indices to Establish Drought Classification Maps of the Ba River Basin in Vietnam

Abstract: The objective of this study was to establish drought classification maps to simulate and calculate the lack of discharge in the Ba River basin in Vietnam. The maps were established using three meteorological drought indices (the Standardized Precipitation Index (SPI), the Drought Index (J), and the Ped Index (Ped)), the Soil and Water Assessment Tool (SWAT) model, and the hydrological drought index (KDrought). The results from the calculation of the SPI, Aridity Index (AI), and Ped at three stations (An Khe, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Hydrological models such as the hydrologic modeling system (HEC-HMS) [7,8], the Australian water balance model (AWBM) [9], the soil moisture accounting and routing (SMAR) model [10], the topography-based hydrological model (TOPMODEL) [11,12] and the soil and water assessment tool (SWAT) [13] are useful for simulating the runoff from ungauged catchment based on the data availability and complexity of the hydrological system. Many studies have demonstrated that SWAT is an effective and promising tool to use for simulating flows and sediments for large-scale watersheds and complex basins with different land uses and various soil types (Access et al [14], Brouziyne et al [15], Palani et al [16], Amatya et al [17], and Tri et al [18], among others). The advantages of using SWAT include its applicability to larger watersheds with more than 100 km 2 , its interface with a geographic information system (GIS), its ability to perform continuous simulations, and its ability to characterize a watershed in high spatial detail [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models such as the hydrologic modeling system (HEC-HMS) [7,8], the Australian water balance model (AWBM) [9], the soil moisture accounting and routing (SMAR) model [10], the topography-based hydrological model (TOPMODEL) [11,12] and the soil and water assessment tool (SWAT) [13] are useful for simulating the runoff from ungauged catchment based on the data availability and complexity of the hydrological system. Many studies have demonstrated that SWAT is an effective and promising tool to use for simulating flows and sediments for large-scale watersheds and complex basins with different land uses and various soil types (Access et al [14], Brouziyne et al [15], Palani et al [16], Amatya et al [17], and Tri et al [18], among others). The advantages of using SWAT include its applicability to larger watersheds with more than 100 km 2 , its interface with a geographic information system (GIS), its ability to perform continuous simulations, and its ability to characterize a watershed in high spatial detail [19].…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam is likely to be one of the countries most affected by climate change because of its long coastline and strong reliance on agriculture, natural resources, and forestry [34,[38][39][40][41]. Few publications have investigated the characteristics of droughts in this region (e.g., [32,35,[42][43][44][45]). Tue and co-authors [32] investigated drought over the Central Highland using the Standardized Precipitation Index (SPI) with different observed and modeled monthly precipitation datasets for the period 1990-2005.…”
Section: Introductionmentioning
confidence: 99%
“…Although the country is narrow, spatial differences of meteorological drought severity for South Central and the Central Highlands are documented [42]. In the north of the country, the Cai River Basin has also experienced relatively high drought severity in the period of 1982 to 2012 [43], while extreme drought affected the Ba River basin in South-Central Vietnam during 2013 and 2016 [44]. Other authors, such as Vu-Thanh et al [45], investigated the occurrence of drought through several drought indices for the period 1961-2007, considering Vietnam divided into seven sub-regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Droughts have considerable economic, societal, and environmental impacts. Drought can typically be classified into four types depending on different kinds of drought impacts in different areas: meteorological, hydrological, agricultural and socioeconomic (Hasan et al, 2019;Tri et al, 2019). Any types of drought are dynamic and defined by various characteristics such as frequency, severity, duration, and magnitude.…”
Section: Introductionmentioning
confidence: 99%